Peningkatan Kapasitas Kelompok Tani Melalui Pelatihan Pembuatan Kompos Berbasis Sampah Organik di Desa Pocangan, Kecamatan Sukowono, Kabupaten Jember - Arisandi, Dewi Puspa; Yulianto, Ma’ruf; Nailurrakhman, Adrian; Savero, Fernanda; Aurellia, Tiffany; Alwi, Kharisma Shofiudin Ma’sum; Nisa, Ulfi Khorun; Halimah, Nur; Rejeki, Desi; Anindita, Devina Cinantya (JATIMAS : Jurnal Pertanian dan Pengabdian Masyarakat, 2025)
Pocangan Village is located in Jember Regency, where the majority of the population works as farmers. These farmers are highly dependent on the availability of inorganic fertilizers, which are becoming increasingly scarce, expensive, and have been shown to reduce soil fertility. Organic waste is abundantly found in Pocangan Village and has the potential to be recycled into compost that is more environmentally friendly and aligns with the principles of sustainable agriculture. The objective of this community service activity was to provide training on the production of compost from organic waste to enhance the capacity of farmers in Pocangan Village. The activity was conducted from July to August 2023. Knowledge transfer to the farmers was carried out in three stages: (1) presentation of the material, (2) assistance in compost production, and (3) evaluation. The presentation phase involved lectures and demonstrations of the composting process to 12 farmers. Assistance was then provided to two farmers who practiced the compost-making process firsthand and applied the compost to their crops. An evaluation was conducted to measure the farmers' knowledge, skills, and satisfaction before and after the activity using a questionnaire. The questionnaire consisted of eight questions and was administered to all 12 farmer participants as respondents. The compost training based on organic waste successfully increased the farmers' capacity to recycle organic waste into compost by 82.29%. The training also contributed to reducing farmers' dependency on inorganic fertilizers and addressed the issue of unmanaged organic waste in the village. Desa Pocangan terletak di Kabupaten Jember yang sebagian besar masyarakatnya berprofesi sebagai petani. Petani sangat bergantung pada ketersediaan pupuk anorganik yang saat ini semakin langka, harganya mahal, dan terbukti menurunkan kesuburan tanah. Sampah organik banyak di temukan di Desa Pocangan dan berpotensi di daur ulang menjadi kompos yang lebih ramah lingkungan dan sesuai dengan prinsip pertanian berkelanjutan. Tujuan kegiatan Pengabdian kepada Masyarakat adalah memberikan pelatihan pembuatan kompos berbasis sampah organik untuk meningkatkan kapasitas petani di Desa Pocangan. Kegiatan dilaksanakan pada bulan Juli - Agustus 2023. Transfer pengetahuan kepada petani dilakukan melalui 3 tahap, yaitu 1) pemaparan materi, 2) pendampingan pembuatan kompos, dan 3) evaluasi. Pemaparan materi dilakukan dengan metode ceramah dan demonstasi proses pembuatan kompos kepada 12 orang petani. Pendampingan dilakukan kepada 2 orang petani yang mempraktikkan langsung pembuatan kompos sampai aplikasi ke tanaman. Evaluasi dilakukan untuk mengukur pengetahuan, keterampilan, dan kepuasan petani sebelum dan sesudah kegiatan menggunakan kuisioner. Kuisioner terdiri dari 8 pertanyaan yang diberikan kepada 12 orang petani peserta pelatihan sebagai responden. Pelatihan pembuatan kompos berbasis sampah organik dapat meningkatkan kapsitas petani dalam mendaur ulang sampah organik menjadi kompos sebesar 82,29%. Pelatihan dapat mengatasi masalah ketergantungan petani terhadap pupuk anorganik dan keberadaan sampah organik di desa.